Development of Interactive E-Modules for Elementary Students: Enhancing Learning Outcomes - Safitri, Tri Rika; Dafit, Febrina (PrimaryEdu : Journal of Primary Education, 2025)
This study aims to develop an interactive e-module that can improve elementary school students' learning outcomes and provide a more interesting learning experience. The method used is research and development (R&D) with the ADDIE model. Data collection was carried out through questionnaires, interviews, tests, and document recording, which were analyzed using a Likert scale. The validation results showed that the e-module design scored 95%, the material scored 73%, and the language scored 92.5%. Responses from teachers (91.47%) and students (90%) showed that this e-module was interesting, effective, and could help students understand the material better. The effectiveness test showed a significant influence on student learning outcomes (significance value 0.000), which proves that this e-module is more effective than conventional learning methods. The implications of this study are that the e-module developed is proven to be valid, practical, and effective and can be used as an interactive and enjoyable learning medium to improve student learning outcomes and motivation, especially in overcoming monotonous learning challenges.